2016
DOI: 10.1128/jvi.01096-16
|View full text |Cite
|
Sign up to set email alerts
|

Protective Capacity of the Human Anamnestic Antibody Response during Acute Dengue Virus Infection

Abstract: Half of the world's population is exposed to the risk of dengue virus infection. Although a vaccine for dengue virus is now available in a few countries, its reported overall efficacy of about 60% is not ideal. Protective immune correlates following natural dengue virus infection remain undefined, which makes it difficult to predict the efficacy of new vaccines. In this study, we address the protective capacity of dengue virus-specific antibodies that are produced by plasmablasts a few days after natural secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…ELISA plates were coated with anti-V5 tag antibodies, followed by incubation of V5-tagged wildtype or mutated E proteins produced in S2 cells. This indirect ELISA method facilitates immobilization of E protein as dimers and the method and its validation have been described in detail before (Xu et al, 2016). Each serum sample was incubated on 12 E protein mutants and the WT E protein.…”
Section: Epitope Binding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISA plates were coated with anti-V5 tag antibodies, followed by incubation of V5-tagged wildtype or mutated E proteins produced in S2 cells. This indirect ELISA method facilitates immobilization of E protein as dimers and the method and its validation have been described in detail before (Xu et al, 2016). Each serum sample was incubated on 12 E protein mutants and the WT E protein.…”
Section: Epitope Binding Studiesmentioning
confidence: 99%
“…Therefore, we tested whether the serum from individuals with past SD and NSD had different repertoires, particularly with regards to fusion-loop specificity. We used 12 alanine-replacement E protein mutants from DENV-2 to test loss of binding to the mutated E protein dimers in the sera of all individuals (Xu et al, 2016). Three mutations were in the fusion loop whereas the other nine were reported previously to be dominant epitopes of patient-derived monoclonal antibodies (Dejnirattisai et al, 2015).…”
Section: Difference In Dengue Igg Antibody Levels Dengue E Proteins mentioning
confidence: 99%
“…At high concentrations, cross-reactive antibodies induce the formation of large viral aggregates able to cross-link inhibitory FcγRIIB, thereby blocking infection and avoiding ADE [ 116 ]; however, as their levels are declining over time, there is an increased risk of ADE due to sub-neutralising antibody concentrations [ 30 ]. Upon secondary infection with a heterologous DENV serotype, cross-reactive MBCs generated during primary infection preferentially expand and dominate over serotype-specific responses [ 70 , 111 , 112 , 115 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. The resulting cross-reactive antibodies were shown to have higher binding avidities and neutralising potencies than those found in primary DENV infection, being able to neutralise not only the current and previous infecting serotype but also serotypes to which individuals have not yet been exposed (‘non-exposed’ serotypes) [ 112 , 113 , 117 , 118 , 124 , 125 , 126 ].…”
Section: Neutralising Antibodies Against Denvmentioning
confidence: 99%
“…Several screening studies observed immunodominance of the EDI/II region in DENV-immune donors and found that it was mainly targeted by cross-reactive antibodies displaying weak neutralising activity [ 104 , 105 , 106 , 110 , 121 , 142 , 143 , 144 , 145 ]. The majority of these antibodies have been mapped to a region comprising the FL in EDII (amino acids 98 to 110), termed the fusion loop epitope (FLE) [ 71 , 104 , 105 , 110 , 123 , 142 , 144 , 146 ]. Trp101 has been identified as a key residue for the binding of various mAbs to the FLE, with many also being sensitive to substitution of the neighbouring residues Gly106, Leu107, and Phe108 [ 104 , 105 , 109 , 123 , 125 , 147 , 148 , 149 , 150 ].…”
Section: Neutralising Antibodies Against Denvmentioning
confidence: 99%
See 1 more Smart Citation